Seifert fibered spaces: triangulation and recognition - Jackson, A (2023)
In this thesis, we study 3-manifolds from an algorithmic point of view. Our motivation is the conjecture that 3-manifold homeomorphism is in NP. The hope is that if one can prove this conjecture in the special case of geometric 3-manifolds, then one can use geometrisation to prove the general statement. This thesis predominantly concerns itself with the Seifert fibered case.